0711 Select Symptoms From The Epworth Sleepiness Scale Questionnaire And Response To Therapy Of Central Sleep Apnea With Phrenic Nerve Stimulation. (27th May 2020) - Javaheri, S; McKane, S; Meyer, T E; Germany, R
Abstract: Introduction: Some subjects with central sleep apnea (CSA) complain of subjective excessive daytime sleepiness (EDS), as assessed by the Epworth Sleepiness Score (ESS). However, there is considerable variability in the level of chances of dozing for each of the 8 ESS questions, as each reflects a different situation. The aim of this analysis was to examine individual situations of the ESS and determine if transvenous phrenic nerve stimulation (TPNS) resulted in improvements of individual ESS situations which were scored moderate to high (2 and 3) at baseline. Patient Global Assessment (PGA) was also assessed. Methods: All 151 subjects enrolled in the randomized (Treatment vs Control) rem edē System pivotal trial were included in the analysis. All subjects were implanted, but activation in Control arm was delayed 6 months. Results: Greater than or equal to 50% of patients scored moderate-high on several individual ESS situations: chance of dozing while sitting and reading (57%), watching television (62%), while lying down to rest in the afternoon when circumstances permit (76%). In the active arm, 68%, 44% and 29% of patients with moderate-high at baseline, respectively, for sitting and reading, watching television, and lying down to rest in the afternoon shifted to less than moderate at 6 months. Respective shifts for the control arm were 29%, 23% and 13%. Seventy-two percent of treated subjects with baseline ESS>10 shifted to ≤10 at 6 months compared to 26% of control patients. Additionally, 72% of treated compared to 7% of control subjects with baseline ESS>10 reported markedly or moderately improved QoL. Conclusion: Results of this randomized controlled trial shows that compared to the control arm, TPNS leads to improvements in various situations of the ESS as well as QoL. The most improved situations were less chance of dozing while reading and watching television. Support: Respicardia